2019
DOI: 10.1111/cts.12691
|View full text |Cite
|
Sign up to set email alerts
|

Variability in In Vitro OATP1B1/1B3 Inhibition Data: Impact of Incubation Conditions on Variability and Subsequent Drug Interaction Predictions

Abstract: As the research into the organic anion transporting polypeptides (OATPs) continues to grow, it is important to ensure that the data generated are accurate and reproducible. In the in vitro evaluation of OATP1B1/1B3 inhibition, there are many variables that can contribute to variability in the resulting inhibition constants, which can then, in turn, contribute to variable results when clinical predictions (R‐values) are performed. Currently, the only experimental condition recommended by the US Food and Drug Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The reported differences in inhibitory properties of TKIs toward the function of transporters such as OATP1B1 as a function of the test substrate used in in vitro studies can directly impact calculated R-values, and influence the reliability of DDI predictions and the clinical decision-making process, especially for weak-to-moderate inhibitors [ 74 ]. Incubation conditions: Several studies have demonstrated that the mechanism by which TKIs inhibit the function of OATP1B1 and/or OATP1B1 can be time-dependent [ 75 ], for example in the case of pazopanib, where preincubation times are inversely correlated with the degree of transport inhibition such as that longer preincubation times result in lower IC 50 estimates [ 72 ]. The FDA guidance recommends the inclusion of a preincubation condition, in addition to simultaneous incubation of inhibitor and substrate, to ensure that optimal prediction values can be derived from in vitro experiments.…”
Section: Effects Of Tkis On the Function Of Oatp1b1 And Oatp1b3mentioning
confidence: 99%
See 3 more Smart Citations
“…The reported differences in inhibitory properties of TKIs toward the function of transporters such as OATP1B1 as a function of the test substrate used in in vitro studies can directly impact calculated R-values, and influence the reliability of DDI predictions and the clinical decision-making process, especially for weak-to-moderate inhibitors [ 74 ]. Incubation conditions: Several studies have demonstrated that the mechanism by which TKIs inhibit the function of OATP1B1 and/or OATP1B1 can be time-dependent [ 75 ], for example in the case of pazopanib, where preincubation times are inversely correlated with the degree of transport inhibition such as that longer preincubation times result in lower IC 50 estimates [ 72 ]. The FDA guidance recommends the inclusion of a preincubation condition, in addition to simultaneous incubation of inhibitor and substrate, to ensure that optimal prediction values can be derived from in vitro experiments.…”
Section: Effects Of Tkis On the Function Of Oatp1b1 And Oatp1b3mentioning
confidence: 99%
“… Cell line selection: Although regulatory guidance documents do not currently expressly specify any particular cell-based model system for standardized use in in vitro transporter studies, prior findings have supported the notion that the choice of cell lines used for transfection can influence conclusions about inhibitory properties of xenobiotics. Indeed, McFeely et al have argued that the selection of cell lines as one of the most important factors contributing to variability in observed OATP-mediated transport inhibition when using in vitro models [ 75 ]. In addition to intrinsic differences between commonly used cell lines that may be linked with differential baseline expression of other transport mechanisms of putative relevance and artificial compensatory dysregulation of other transporters in overexpressed models, factors such cell origin (e.g., mammalian vs amphibian), cell passage number, cell culture conditions, and maintenance procedures, seeding density, media composition (e.g., presence of binding proteins), and duration of time that cells are in culture (e.g., expression drifting), which are often not clearly documented, could further affect the outcome of each study [ 77 ].…”
Section: Effects Of Tkis On the Function Of Oatp1b1 And Oatp1b3mentioning
confidence: 99%
See 2 more Smart Citations
“…For the determination of IC50 values of OATP1B1/1B3, cell type and preincubation with the inhibitor have been identified as the two main sources of variability. However, they did not show a strong effect on R‐value prediction relative to the FDA evaluation cutoff of 1.1 (McFeely et al., 2020).…”
Section: Evaluation Of Tddismentioning
confidence: 99%